CASP9 genotype confers gentamicin susceptibility in intratympanic treatment of intractable vertigo caused by Ménière's disease. (3rd April 2019) - Huang, Chi-Jung; Wan, Tan-Kuai; Fang, Te-Yung; Wang, Pa-Chun
Abstract: Background: Ménière's disease (MD) is a disorder of the inner ear, causing episodes of vertigo. Although surgery is reserved for intractable MD, intratympanic gentamicin (ITG) injection has become an alternative for controlling vertigo. Aims/Objectives: To investigate the genetic basis of ITG efficacy. Material and methods: We hypothesized that single nucleotide polymorphisms (SNPs) affect outcomes in patients with MD who receive ITG injections. Whole-exome sequencing was used to determine variations in coding regions. Results: Multivariate analysis revealed two SNPs, rs1052571 in caspase 9 (CASP9; p = .017) and rs3745274 in cytochrome P450 2B6 ( p = .053), which were associated with susceptibility to ITG injections. Only the C-allele in the rs1052571 SNP was significantly associated with susceptibility ( p = .027; odds ratio: 5.95; 95% confidence interval: 1.26–28.57, by Fisher's exact test). Conclusions and significance: Our results elucidated the role of the rs1052571 SNP and provide a genetic perspective on gentamicin efficacy (susceptibility) in treating intractable MD.